Saprobic fungi on dead wild banana - Photita W. (2014)
Saprobic fungi associated with dead tissue of Musa acuminata from five sites at Doi Suthep Pui National Park, Thailand were investigated. Nine hundred collections of decaying Musa were examined and 80 fungal species were identified, comprising 7 ascomycetes, 2 basidiomycetes and 71 anamorphic fungi (4 coelomycetes and 67 hyphomycetes). The most commonly encountered species were Periconia digitata, Verticillium tenuissimum, Memnoniella subsimplex and Pseudobotrytis terrestris, which were represented by 32%, 19%, 15% and 14% of the total collections, respectively. The site of collection did not significantly affect fungal species composition. However, the fungal communities on leaves were markedly different from those on petioles and pseudostems.